Risk Factors and Outcome of Acute Kidney Injury in Critical COVID-19 patients in Karachi, Pakistan: A Single center, Retrospective study - Haider, Anam; Shalim, Elisha; Afzal, Sidra (Pakistan Journal of Kidney Diseases, 2023)
Introduction: The severe acute respiratory syndrome coronavirus2 (SARS-CoV2) is a novel beta-coronaviridae family and its effects on the kidneys have been reported which included the increased requirement of renal replacement therapy during the Covid-19 pandemic. Our study is,thus, designed to determine the risk factors of AKI in critically ill patients with covid-19 and their outcomes Method and Material: It is a retrospective observational study of COVID-19 patients admitted in SIDH&RC(specialized facility center for COVID-19) from July 2020 to July 2021. The patients were divided into two groups; one with confirmed critical COVID-19 and had AKI during hospital stay and the other group who have confirmed critical COVID-19 and did not had AKI during hospital stay. Results: Total 232 patients included in this study who were critical at the time of admission in which 92(39.65%) of the patients had AKI during hospital stay. Most of the patients who had AKI were male 55(59.8%). We found that in this population mortality was not significant in critical COVID-19 patients with AKI. However, patients with AKI had worst survival distribution compared to non-AKI patients (p<0.05). Patients with AKI required mechanical ventilation compared to non-AKI patients (70.7% vs 50.7%, p<0.05) along with significant chances of occurrence of complications as superimposed bacterial infections (78.3% vs 52.9%, p<0.05), NSTEMI (33.7% vs 13.6%, p<0.05), septic shock (66.3% vs 38.6%, p<0.05) and progression to severe ARDS (78.3% vs 60.7%, p<0.05). Conclusion: We found that patients with AKI had a worst survival distribution than non AKI in Critical COVID-19 patients